ANALISIS MANAJEMEN SYARIAH PERBANDINGAN KINERJA KEUANGAN ANTAR CABANG KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) BAYTUL IKHTIAR (STUDI KASUS CABANG CIPANAS DAN LEUWISADENG, KABUPATEN BOGOR) - Tri Aditya Putra; Tubagus Rifqy Thantawi; Bayu Purnama Putra (SAHID BANKING JOURNAL, 2022)
This study aims to analyze sharia management of financial performance comparisons between Cipanas and Leuwi Sadeng branches at KSPPS Baytul Ikhtiar. The data used is secondary data and the method used is descriptive quantitative with the help of SPSS version 25 to obtain a comprehensive picture of the relationship between one variable and another. The sample selected based on the criteria is 1 company with 2 service branches. Sampling was carried out using field research techniques. The results of this study indicate that by calculating the liquidity ratio there is no difference in financial performance between the Cipanas and Leuwisadeng branches, by calculating the profitability ratio there is no difference in financial performance between the Cipanas and Leuwisadeng branches, by calculating the solvency ratio there is no difference in financial performance between the Cipanas and Leuwisadeng branches, based on the calculation of profitability ratios, there is no difference in financial performance between the Cipanas and Leuwisadeng branches.